Odpowiedzi

Najlepsza Odpowiedź!
2009-10-01T21:12:26+02:00
7x-y+17=0
5x+6y=8

y=17+7x
5x+6y=8

y=17+7x
5x+6(17+7x)=8

y=17+7x
5x+102+42x=8

y=17+7x
47x=-94 /:47

y=17+7x
x=-2

y=17+7*(-2)
x=-2

y=17-14
x=-2

y=3
x=-2
2009-10-01T21:15:18+02:00
7x-y+17=0 /+y
5x+6y=8

y=17-7x
5x+6(17+7x)=8

y=17+7x
5x+102+42=8

y=17+7x
5x=-136 /:5

y=17+7x
x=(-27,2)

y=17+7(-27,2)
x=(-27,2)

y=17-190,4
x=(-27,2)

y=-173,4
x=-27,2
2009-10-01T22:07:30+02:00
7x-y+17=0
5x+6y=8
-y=-17-7x/×(-1)
y=17+7x
5x+6×(17+7x)=8
5x+102+42x=8
47x=8-102
47x=-94/÷47
x=-2
5x+6y=8
5×(-2)+6y=8
-10+6y=8
6y=8+10
6y=18/÷6
y=3

x=-2
y=3